Transient Antiphospholipid Syndrome Associated with Primary Cytomegalovirus Infection: A Case Report and Literature Review - Tsuyoshi Nakayama; Mitsuteru Akahoshi; Kensuke Irino; Yasutaka Kimoto; Yojiro Arinobu; Hiroaki Niiro; Hiroshi Tsukamoto; Takahiko Horiuchi; Koichi Akashi (Case Reports in Rheumatology)
Viral infection is known to induce transient autoimmunity in humans. Acute cytomegalovirus (CMV) infection is implicated in occasional thrombosis formation. We here, for the first time, report a 19-year-old female who had an acute CMV infection, leading to a deep venous thrombosis and a pulmonary embolism along with transient appearance of lupus anticoagulant. The pathological role of antiphospholipid antibodies in CMV-mediated thrombosis is discussed.